Modulation of the Aleutian–Icelandic low seesaw and its surface impacts by the Atlantic Multidecadal Oscillation - Li, Fei; Orsolini, Yvan; Wang, Huijun; Gao, Yongqi; He, Shengping (Advances in Atmospheric Sciences, 2018)
Early studies suggested that the Aleutian–Icelandic low seesaw (AIS) features multidecadal variation. In this study, the multidecadal modulation of the AIS and associated surface climate by the Atlantic Multidecadal Oscillation (AMO) during late winter (February–March) is explored with observational data. It is shown that, in the cold phase of the AMO (AMO|−), a clear AIS is established, while this is not the case in the warm phase of the AMO (AMO|+). The surface climate over Eurasia is significantly influenced by the AMO’s modulation of the Aleutian low (AL). For example, the weak AL in AMO|− displays warmer surface temperatures over the entire Far East and along the Russian Arctic coast and into Northern Europe, but only over the Russian Far East in AMO|+. Similarly, precipitation decreases over central Europe with the weak AL in AMO|−, but decreases over northern Europe and increases over southern Europe in AMO|+. The mechanism underlying the influence of AMO|− on the AIS can be described as follows: AMO|− weakens the upward component of the Eliassen–Palm flux along the polar waveguide by reducing atmospheric blocking occurrence over the Euro–Atlantic sector, and hence drives an enhanced stratospheric polar vortex. With the intensified polar night jet, the wave trains originating over the central North Pacific can propagate horizontally through North America and extend into the North Atlantic, favoring an eastward-extended Pacific–North America–Atlantic pattern, and resulting in a significant AIS at the surface during late winter. acceptedVersion